A microbiota-modulated checkpoint directs immunosuppressive intestinal T cells into cancers - Fidelle, Marine; Rauber, Conrad; Roberti, Maria Paula; Koschny, Ronald (Science, 2023)
Antibiotics (ABX) compromise the efficacy of programmed cell death protein 1 (PD-1) blockade in cancer patients, but the mechanisms underlying their immunosuppressive effects remain unknown. By inducing the down-regulation of mucosal addressin cell adhesion molecule 1 (MAdCAM-1) in the ileum, post-ABX gut recolonization by Enterocloster species drove the emigration of enterotropic α4β7+CD4+ regulatory T 17 cells into the tumor. These deleterious ABX effects were mimicked by oral gavage of Enterocloster species, by genetic deficiency, or by antibody-mediated neutralization of MAdCAM-1 and its receptor, α4β7 integrin. By contrast, fecal microbiota transplantation or interleukin-17A neutralization prevented ABX-induced immunosuppression. In independent lung, kidney, and bladder cancer patient cohorts, low serum levels of soluble MAdCAM-1 had a negative prognostic impact. Thus, the MAdCAM-1-α4β7 axis constitutes an actionable gut immune checkpoint in cancer immunosurveillance.
Gesehen am 26.06.2023